2016
DOI: 10.1016/j.addbeh.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual symptoms and smoking-related expectancies

Abstract: Given that prior research implicates smoking abstinence in increased premenstrual symptoms, tobacco withdrawal, and smoking behaviors, it is possible that women with more severe premenstrual symptoms have stronger expectancies about the effects of smoking and abstaining from smoking on mood and withdrawal. However, such relations have not been previously explored. This study examined relations between premenstrual symptoms experienced in the last month and expectancies that abstaining from smoking results in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Thus, these findings should be interpreted with caution until replicated. These findings expand previous work showing associations between PMS and withdrawal symptoms (Allen, Hatsukami, Christianson, & Nelson, 1999) and expectations that smoking abstinence results in withdrawal (Pang et al, 2016), to suggest that women who experience more severe affective PMS may also experience greater withdrawal during quit attempts. Daytime tobacco dependence has been interpreted to assess the persistence in which nicotine levels are maintained at a given threshold throughout the day (Richardson & Ratner, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, these findings should be interpreted with caution until replicated. These findings expand previous work showing associations between PMS and withdrawal symptoms (Allen, Hatsukami, Christianson, & Nelson, 1999) and expectations that smoking abstinence results in withdrawal (Pang et al, 2016), to suggest that women who experience more severe affective PMS may also experience greater withdrawal during quit attempts. Daytime tobacco dependence has been interpreted to assess the persistence in which nicotine levels are maintained at a given threshold throughout the day (Richardson & Ratner, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…It should also be noted that premenstrual syndrome is experienced during this phase. In fact, two studies in this review (Pang et al, 2016; found a positive correlation between withdrawal symptoms and the presence of premenstrual symptoms. Choi and Hamidovic (2020) have noted that this relationship may be maintained because smoking can help reduce the discomfort caused by premenstrual syndrome, although at the same time they have also found that smoking triggers an increase in these symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…To evaluate the relationship between ovarian hormone levels and smoking behavior. Effect of premenstrual syndrome on withdrawal syndrome Pang et al (2016) To evaluate the relationship between premenstrual symptoms in the past month with expectations of withdrawal syndrome and expectations of positive and negative reinforcement of consumption.…”
Section: Schiller Et Al (2012)mentioning
confidence: 99%